Microcrack plugging agent
By using micro-crack plugging agents composed of biopolymers, calcium carbonate particles, biomass particles and crosslinking agents, the problem of difficulty in sealing and resolving of blocking in the prior art is solved, and the effect of efficient blocking and resolvable is achieved, which is suitable for the micro-crack plugging needs of gas storage storage.
Patent Information
- Application Number
- CN202311152078.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-09-07
AI Technical Summary
When existing micro-crack leak plugging agents are used in gas storage, it is difficult to meet the requirements of sealing and resolving the plugging at the same time, resulting in difficulty in plugging and affecting the production of gas storage.
A micro-crack plugging agent composed of biopolymers, calcium carbonate particles, biomass particles and crosslinking agents is used. The warm-wheel glue and xanthan glue in the biopolymer work together to play the leak plugging effect. The calcium carbonate particles and biomass particles are blocked by bridge action and decomposed under the acid solution to achieve blocking.
It has achieved efficient sealing of micro-cracks, high sealing strength and resolvable, suitable for different production layers, and has good economic, social and environmental benefits.
Smart Images

Figure BDA0004437402800000051 
Figure BDA0004437402800000061 
Figure BDA0004437402800000071
Abstract
Description
Technical Field
[0001] The invention relates to a micro-crack plugging agent, belonging to the technical field of oil and gas reservoir chemicals. Background Art
[0002] Gas storage plays an important role in natural gas peak regulation. Natural gas can be stored in underground gas storage during the off-season and extracted from underground gas storage during the peak season, thereby ensuring the supply and demand of natural gas for people's production and life. Due to alternating pressure changes and formation creep during gas injection and production, the cement ring of the injection and production wells in the gas storage is prone to microcracks, and the crack width is mostly less than 100μm. The appearance of cracks will cause natural gas to surge up. If these microcracks are not blocked in time, they will increase rapidly under the action of production pressure difference, seriously affecting the production of the gas storage, and even causing the injection and production wells to be scrapped. The downhole tubing in the injection and production wells of the gas storage is generally a fixed tubing with a packer. When the leakage layer is below the packer, mechanical plugging cannot be implemented, and chemical plugging has the risk of plugging the layer, which is difficult to plug.
[0003] The micro-crack plugging in the above-mentioned well conditions requires that the plugging agent be evenly dispersed, have good injectability and small particle size; it must not only have plugging performance, but also de-plugging performance, because when the micro-cracks in the leakage layer are plugged, the production layer is easily contaminated, and the contamination needs to be removed to restore the permeability.
[0004] Nanomaterials are the first choice for micro-crack plugging because of their small particle size and can effectively enter micro-nanoscale cracks and pores. Currently, nano-plugging materials mainly include organic nano-plugging agents, inorganic nano-plugging agents (nano-silicon dioxide, nano-calcium carbonate, nano-iron oxide and other nano-materials), and organic / inorganic composite plugging agents. Among them, the plugging strength of organic nano-plugging agents is low, and inorganic nano-plugging agents are prone to flocculation. There are many reports on the combined application of the two materials. The plugging material generated by the hydration bonding of inorganic nanomaterials and organic gelling materials studied by Sun Yingsheng does not shrink in volume after solidification, has a dense and uniform microstructure, and a plugging rate of 99.9%. The plastic viscosity of the plugging agent is less than 40mPa·s, easy to pump, temperature resistant to 120℃, salt resistant to 216000mg / L, and compressive strength ≥30MPa, but inorganic nanomaterials are prone to flocculation and cannot be dissolved.
[0005] Chinese patent document CN110591673B discloses a high-strength sealing plugging agent for oil and water well casing leakage, including 15-20% fluorene-based epoxy resin, 10-12% epoxy resin, 10-12% alkaline phenolic resin, 20-30% solvent, 4-5% coupling agent, 15-20% filler (nano material), 4-5% deaerator, 4-5% cross-linking agent; the deaerator is a modified calcium-based deaerator. The preparation method of the modified calcium-based deaerator includes multiple steps such as reaction-aging-drying-grinding-calcination, and the preparation process is complicated. The dispersion of the nanomaterials in the plugging agent is not good, and it is not environmentally friendly. It belongs to a solidified plugging agent and cannot be dissolved. Summary of the invention
[0006] The purpose of the present invention is to provide a micro-crack plugging agent, which can solve the problem that the current plugging agents cannot simultaneously meet the requirements of plugging and unblocking when used for plugging micro-cracks in gas storage reservoirs.
[0007] In order to achieve the above purpose, the technical solution adopted by the micro-crack plugging agent of the present invention is:
[0008] A micro-crack plugging agent mainly consists of a biopolymer, calcium carbonate particles, biomass particles and a cross-linking agent; the biopolymer mainly consists of Weinberg gum and xanthan gum, and the mass ratio of the Weinberg gum to the xanthan gum is (2-4):1; the mass ratio of the biopolymer, calcium carbonate particles and biomass particles is (0.3-1.5):(1-5):(1-5).
[0009] The micro-fracture plugging agent of the present invention comprises biopolymer, calcium carbonate particles, biomass particles and a cross-linking agent. The thermoplastic rubber in the biopolymer has high temperature resistance and viscosity, and the xanthan gum has good salt resistance. The two are used in combination to synergistically plug leaks and improve the suspension stability of calcium carbonate particles and biomass particles in the liquid phase. The biopolymer contains groups such as carboxyl and hydroxyl groups. After being injected into the formation, it can react with the cross-linking agent to form a stable gel to improve the plugging strength; calcium carbonate particles and biomass particles are used as fillers. After being injected into the formation, they can bridge the crack holes and have good plugging strength. Calcium carbonate particles can be decomposed under acid solution, and acid can be injected to achieve unblocking according to actual needs. Biopolymers, calcium carbonate particles, and biomass particles can play a synergistic role to achieve better plugging effect. The micro-fracture plugging agent of the present invention has good dispersibility in water, does not produce layer burial phenomenon after being injected into the formation, has high plugging strength and is solvable. It is suitable for plugging micro-fractures in production layers that can be protected by sand filling or bridge plugging, and can also be used for plugging micro-fractures in production layers that cannot be protected, and has great economic, social and environmental benefits.
[0010] In order to ensure that the calcium carbonate particles can enter holes or cracks with a diameter of less than 20 μm, so as to achieve the purpose of blocking microcracks, preferably, the particle size of the calcium carbonate particles and the biomass particles is no more than 6.5 μm.
[0011] It can be understood that the microcracks in the present invention refer to cracks with a width less than 100 μm.
[0012] In order to reduce costs and play a good plugging effect, preferably, the biomass particles are selected from one or any combination of bagasse, wood chips, and corn grits.
[0013] It can be understood that bagasse is the residue left after sugarcane is extracted; wood chips refer to the powder left over from wood processing; and corn grits are the powder formed after corn is ground.
[0014] Preferably, the microcrack plugging agent also includes a deoxidizer, which can remove oxygen in the system and improve the stability of the plugging agent slurry.
[0015] Preferably, the deoxidizer is an inorganic deoxidizer and / or an organic deoxidizer. Preferably, the inorganic deoxidizer is a sulfite and / or a thiosulfate. For example, the sulfite is an alkali metal sulfite; the thiosulfate is an alkali metal thiosulfate. Using an alkali metal sulfite or an alkali metal thiosulfate as a deoxidizer has the beneficial effects of good water solubility, low price, high deoxidation efficiency, and no influence on the cross-linking reaction.
[0016] Preferably, the crosslinking agent is an organometallic crosslinking agent and / or an aldehyde crosslinking agent. The organometallic crosslinking agents and / or aldehyde compounds applicable to plant gum are applicable to the present invention. For example, the organometallic crosslinking agent is an organic chromium crosslinking agent and / or an organic zirconium crosslinking agent; the aldehyde crosslinking agent is a dialdehyde compound, and the carbon atoms of the dialdehyde compound are 2 to 8. For example, the dialdehyde compound is selected from one or any combination of glyoxal, malondialdehyde and succinaldehyde.
[0017] Further preferably, the crosslinking agent is composed of an organic metal crosslinking agent and an aldehyde crosslinking agent, and the mass ratio of the organic metal crosslinking agent to the aldehyde crosslinking agent is (1-2):(2-4). For example, the mass ratio of the organic metal crosslinking agent to the aldehyde crosslinking agent is (1-1.8):(2-4). The carboxyl group, hydroxyl group and other groups in the biopolymer can undergo a crosslinking reaction with trivalent and polyvalent metals to form a gel, and the aldehyde compound can undergo a hydroxyethylation reaction with the biopolymer to further polymerize and enhance the gel strength.
[0018] Preferably, the mass ratio of the biopolymer, calcium carbonate particles, biomass particles and cross-linking agent is (0.3-1.5):(1-5):(1-5):(0.3-6).
[0019] Preferably, the mass ratio of the biopolymer, calcium carbonate particles, biomass particles, deoxidizer and crosslinker is (0.3-1.5):(1-5):(1-5):(0.01-0.07):(0.3-6). For example, the mass ratio of the biopolymer, calcium carbonate particles, biomass particles, deoxidizer and crosslinker is (0.6-1.5):(1-2):(1-2):(0.02-0.07):(3-6).
[0020] For the convenience of direct use, preferably, the microcrack plugging agent also includes water. When the plugging agent contains water, the biopolymer in the plugging agent can improve the suspension stability of calcium carbonate particles and biomass particles, and give the plugging agent better salt resistance, temperature resistance and shear thinning properties, thereby improving the injectability of the plugging agent.
[0021] The water in the micro-crack plugging agent of the present invention can be deionized water, tap water, or oil field injection water. According to the results of the indoor plugging agent slurry suspension stability test, the total mineralization of the water is ≤30×10 4 mg / L.
[0022] Preferably, the mass fraction of the biopolymer in the microcrack plugging agent is 0.3-1.5%. For example, the mass fraction of the biopolymer in the microcrack plugging agent is 0.6-1.5%. When the mass fraction of the biopolymer in the microcrack plugging agent is 0.3-1.5%, the plastic viscosity of the microcrack plugging agent of the present invention is lower than 40 mPa·s, and the concentration resistance is 30×10 4 The salt of 1000 mg / L can be suspended stably for more than 5 hours at 110°C, is easy to inject and has no coagulation; the micro-fracture plugging agent of the present invention has a plugging rate of more than 99.5% for a 20mD core and a pressure difference of 10MPa.
[0023] Preferably, the microcrack plugging agent is composed of the following components in mass fractions: 0.6-1.5% biopolymer, 1-2% calcium carbonate particles, 1-2% biomass particles, 0.02-0.07% deoxidizer, 3-6% crosslinking agent, and the balance is water.
[0024] Preferably, the microcrack plugging agent is used for mineralization ≤15×10 4 mg / L, sealing of cracks in formations with formation temperature ≤110℃.
[0025] During the injection of the micro-fracture plugging agent of the present invention into the formation, the micro-fracture plugging agent preferentially enters the leakage layer with lower pressure. Under the action of the pressure difference, the rigid particles in the micro-fracture plugging agent are accumulated and bridged in the middle of the micro-fracture, the biopolymer with good fluidity enters the front part and gradually forms a biogel, and the plugging agent at the tail of the fracture gradually forms a mixed gel composed of the biogel and the rigid particles. The front part and the tail part have certain waterproof and acid-alkali resistant effects. A small amount of plugging agent enters the production layer, and a small amount of acid can be added to replace it into the formation, thereby eliminating the damage to the production layer.
[0026] Preferably, the microcrack plugging agent is prepared by a method comprising the following steps:
[0027] (1) mixing the calcium carbonate particles, biomass particles and deoxidizer in a formulated amount with a portion of water to obtain a dispersion;
[0028] Mixing a formulated amount of biopolymer and a portion of water to obtain a suspension;
[0029] (2) mixing the suspension and the dispersion to obtain a mixed solution;
[0030] (3) mixing the mixed solution, the cross-linking agent in the formula amount and the remaining water to obtain a micro-crack plugging agent;
[0031] The amount of water used in preparing the dispersion is 25-35% of the total water, and the amount of water used in preparing the suspension is 45-55% of the total water.
[0032] Preferably, the time for mixing the formulated amount of biopolymer and part of water is 1 to 2 hours.
[0033] Preferably, the method for mixing the suspension and the dispersion comprises the following steps: adding the suspension to the dispersion in a stirring state, and after the suspension is added, continuing to mix until the system is evenly dispersed. Experimental results show that when the dispersion is added to the suspension or the suspension and the dispersion are added at the same time, the prepared microcrack plugging agent will agglomerate when left at 60°C for 5 hours, affecting the injectability and use effect.
[0034] Preferably, the suspension is added at a rate of 10 to 15 mL / min.
[0035] In order to reduce costs and ensure uniform mixing of the raw materials, preferably, stirring is used for uniform mixing when preparing the dispersion. Preferably, the stirring speed when preparing the dispersion is not less than 1000 r / min.
[0036] In order to reduce costs and ensure uniform mixing of the raw materials, preferably, stirring is used for uniform mixing when preparing the suspension. Preferably, the stirring speed when preparing the suspension is not less than 1000 r / min. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0038] The microcrack plugging agent of Examples 1-9 is composed of biopolymer, calcium carbonate particles, biomass particles, deoxidizer, cross-linking agent and water, wherein the biopolymer is composed of weinberg gum and xanthan gum, the deoxidizer is sodium sulfite and / or sodium thiosulfate, the cross-linking agent is composed of organic metal cross-linking agent and aldehyde cross-linking agent, the organic metal cross-linking agent is chromium acetate and / or zirconium acetate, and the aldehyde cross-linking agent is glyoxal.
[0039] The particle sizes of the calcium carbonate particles in the microcrack plugging agents of Examples 1-9 are 2000 mesh, 5000 mesh, 2000 mesh, 3000 mesh, 3000 mesh, 6000 mesh, 8000 mesh, 2000 mesh, and 5000 mesh, respectively; the biomass particles in the microcrack plugging agents of Examples 1-9 are all bagasse, and the particle sizes are 2000 mesh, 5000 mesh, 2000 mesh, 3000 mesh, 3000 mesh, 2000 mesh, 3000 mesh, 2000 mesh, and 2000 mesh, respectively.
[0040] The mass fractions of gum succinate and xanthan gum in the biopolymer, the mass fractions of calcium carbonate particles and biomass particles, the mass fractions of sodium sulfite and / or sodium thiosulfate in the deoxidizer, the mass fractions of organic chromium crosslinker and / or organic zirconium crosslinker and glyoxal in the crosslinker, and the mass fraction of water in each embodiment are shown in Table 1, respectively.
[0041] Table 1 The mass fractions of each raw material in the microcrack plugging agent of each embodiment
[0042]
[0043] The microcrack plugging agent of Examples 1-9 is prepared by a method comprising the following steps:
[0044] (1) At a speed of 2000 r / min, the formulated amount of calcium carbonate particles, biomass particles and deoxidizer are added to a portion of water (the amount of water is 30% of the total amount of water), and stirred evenly to obtain a dispersion; at a speed of 1000 r / min, the formulated amount of biopolymer is added to a portion of water (the amount of water is 50% of the total amount of water), and stirred for 2 hours to obtain a suspension;
[0045] (2) slowly adding the suspension (addition rate is 15 mL / min) into the dispersion in a stirring state, and after sufficient stirring, obtaining a mixed solution;
[0046] (3) Add the formulated amount of cross-linking agent to the mixed solution, then add the remaining amount of water, and stir for 0.5 hours to obtain a micro-crack plugging agent.
[0047] Comparative Example 1
[0048] The plugging agent of this comparative example is different from the plugging agent of Example 1 only in that the mass fraction of xanthan gum in the plugging agent of this comparative example is 15 parts, and the mass fraction of Wenlun gum is 0 parts.
[0049] Comparative Example 2
[0050] The plugging agent of this comparative example is different from the plugging agent of Example 1 only in that the mass fraction of xanthan gum in the plugging agent of this comparative example is 0 parts, and the mass fraction of Wenlun gum is 15 parts.
[0051] Comparative Example 3
[0052] The only difference between the plugging agent of this comparative example and the plugging agent of Example 1 is that the mass fraction of chromium acetate in the plugging agent of this comparative example is 0 parts, and the mass fraction of glyoxal is 56 parts.
[0053] Comparative Example 4
[0054] The only difference between the plugging agent of this comparative example and the plugging agent of Example 1 is that the mass fraction of chromium acetate in the plugging agent of this comparative example is 56 parts, and the mass fraction of glyoxal is 0 parts.
[0055] Comparative Example 5
[0056] The only difference between the plugging agent of this comparative example and the plugging agent of Example 1 is that the mass fraction of calcium carbonate particles in the plugging agent of this comparative example is 20 parts, and the mass fraction of bagasse is 0 parts.
[0057] Comparative Example 6
[0058] The only difference between the plugging agent of this comparative example and the plugging agent of Example 1 is that the mass fraction of calcium carbonate particles in the plugging agent of this comparative example is 0 parts, and the mass fraction of bagasse is 20 parts.
[0059] Experimental example
[0060] In order to evaluate the physical properties of different plugging agents and the plugging effect on microcracks, the rheological properties, suspension stability, plugging performance and solvability of each plugging agent were tested respectively. Among them, the rheological test method is as follows: the viscosity of each plugging agent at different speeds is measured using a ZNN-D6 type rotational viscometer, and then the plastic viscosity is calculated. The test and calculation results are shown in Table 2. The suspension stability test method is as follows: the plugging agent is prepared according to the preparation method of the plugging agent of Examples 1-9 and Comparative Examples 1-6, except that the mass fraction of the cross-linking agent used in the preparation of each plugging agent is 0, and the water used in the preparation is a mineralization degree of 30×10 4mg / L simulated water, and then the prepared plugging agents were left to stand for 5 hours at different temperatures to observe whether stratification, water precipitation, and precipitation occurred. If not, the test result was stable. If stratification, water precipitation or precipitation occurred, the test result was unstable. The test results are shown in Table 2. The plugging performance is expressed by the plugging rate, which is measured by a core displacement test device. The test method is carried out in accordance with 6.7 of the standard Q / SH CG0141-2021 (Sinopec Group Enterprise Standard). First, a sand-filled pipe with a permeability of about 20mD is filled with clean quartz sand, and then the plugging agent is placed in an intermediate container, and then the plugging agent is injected into the sand-filled pipe with a horizontal flow pump. The injected PV number is 2.5, and then the sand-filled pipe is placed in an oven at 110°C for 24 hours, and then the permeability of the sand-filled pipe after the plugging agent is injected is tested, and then the breakthrough pressure is tested. The test results are shown in Table 3. The test method for solvability is as follows: the plugging agent is allowed to stand at formation temperature (110°C) to form a gel, and then the gel is added to hydrochloric acid and soaked to observe whether the gel becomes loose or precipitated. If the above phenomenon occurs, the test result is solvable. If no looseness or precipitate occurs, the test result is unsolvable. The test results are shown in Table 3.
[0061] Table 2 Rheological properties and suspension stability test results of each plugging agent
[0062]
[0063]
[0064] Table 3 Test results of plugging performance and solvability of each plugging agent
[0065]
[0066]
[0067] As shown in Table 2, the plastic viscosity of the plugging agent of Examples 1-9 is not more than 40mPa·s, and it is easy to pump. After the plugging agent of Example 1-9 (without a cross-linking agent) is left at 60-110°C for 5h, there is no stratification, water separation, precipitation and the like, indicating that the plugging agent of Example 1-9 (without a cross-linking agent) has excellent suspension stability, which can ensure safe injection during construction and prevent solid phase particles from settling and blocking the wellbore at the bottom of the well. As shown in Table 3, the plugging rate of the plugging agent of Example 1-9 exceeds 99.5%, and the breakthrough pressure is not less than 10MPa, indicating that the plugging agent of Example 1-9 has good plugging ability, can meet the plugging needs of micro-cracks in the injection and production wells of the on-site gas storage reservoir, and has solvability.
[0068] After replacing the chromium acetate in Examples 1-9 with chromium lactate, the performance (rheology, suspension stability, plugging performance and solvability) remained unchanged.
[0069] After replacing the bagasse in Example 1 with sawdust or corn grits with a particle size of no more than 6.5 μm, when the rheological properties, suspension stability, plugging performance and solvability were tested according to the above test methods, the test results were close to the corresponding test results of Example 1.
Claims
1. A micro crack plugging agent, characterized in that: The invention mainly consists of biopolymer, calcium carbonate particles, biomass particles and a cross-linking agent; the biopolymer mainly consists of gum bismuth and xanthan gum, and the mass ratio of gum bismuth and xanthan gum is (2-4):1; the mass ratio of biopolymer, calcium carbonate particles and biomass particles is (0.3-1.5):(1-5):(1-5).
2. The microcrack plugging agent according to claim 1, characterized in that: The particle sizes of the calcium carbonate particles and the biomass particles are both no greater than 6.5 μm.
3. The microcrack plugging agent according to claim 1 or 2, characterized in that: The biomass particles are selected from one or any combination of bagasse, wood chips and corn grits.
4. The microcrack plugging agent according to claim 1 or 2, characterized in that: The mass ratio of the biopolymer, calcium carbonate particles, biomass particles and cross-linking agent is (0.3-1.5):(1-5):(1-5):(0.3-6).
5. The microcrack plugging agent according to claim 1 or 2, characterized in that: The micro-crack plugging agent also includes a deoxidizer; the deoxidizer is an inorganic deoxidizer and / or an organic deoxidizer; the inorganic deoxidizer is a sulfite and / or a thiosulfate.
6. The microcrack plugging agent according to claim 5, characterized in that: The sulfite is an alkali metal sulfite; and the thiosulfate is an alkali metal thiosulfate.
7. The microcrack plugging agent according to claim 5, characterized in that: The mass ratio of the biopolymer, calcium carbonate particles, biomass particles, deoxidizer and crosslinking agent is (0.6-1.5):(1-2):(1-2):(0.02-0.07):(3-6).
8. The microcrack plugging agent according to claim 1 or 2, characterized in that: The cross-linking agent is an organic metal cross-linking agent and / or an aldehyde cross-linking agent; the aldehyde cross-linking agent is a dialdehyde compound, and the dialdehyde compound is selected from one or any combination of glyoxal, malondialdehyde and succinaldehyde.
9. The microcrack plugging agent according to claim 8, characterized in that: The cross-linking agent is composed of an organic metal cross-linking agent and an aldehyde cross-linking agent, and the mass ratio of the organic metal cross-linking agent to the aldehyde cross-linking agent is (1-2):(2-4).
10. The microcrack plugging agent according to claim 1 or 2, characterized in that: The plugging agent also includes water; the mass fraction of the biopolymer in the plugging agent is 0.6-1.5%.
Citation Information
Patent Citations
A high-strength sealing and plugging agent
CN110591673B
Aqueous-based hydrolytically stable dispersion of a biodegradable polymer
CN109071828A
Composite plugging agent bridge plug plugging particles for drilling fluid
CN111808583A
Method for creating dense drilling fluid additive and composition therefor
US20020147113A1
Well plug additive, well plug treatment fluid made therefrom, and method of plugging a well
US20040020651A1